KANDUNGAN GULA DALAM MINUMAN TEH SUSU DENGAN TOPPING BOBA DI KALANGAN MAHASISWA DEPOK DAN JAKARTA - Mayrlnn Trifosa Veronica (2020)
Boba milk tea which known originated from Taiwan, has become a popular beverage throughout the world, including in Indonesia especially among the youths and young adults. Boba milk tea contains high sugar and calorie levels and is part of the larger group of sugar sweetened beverages (SSBs) which generally sweetened with high fructose corn syrup or sucrose. SSBs have become a major contributor to added sugar consumption which correlates with the increased global prevalence of overweight or obesity. This descriptive observational study aims to analyze the sugar level (fructose, glucose, sucrose) contained in boba milk tea chosen by Depok and Jakarta undergraduate students based on the results of pre-study questionnaire. Analysis of sugar and other nutrients were carried out in an accredited laboratory. The sugar composition analysis was performed by high performance liquid chromatography (HPLC), calorific values were determined by calculation, and the analyses were repeated twice. Results suggest that the sugar content in milk tea drinks consumed with boba topping fulfilled 94.4% of the daily limit of sugar consumption recommended by the Ministry of Health of the Republic of Indonesia, and contributed as much as 33.75% of the energy requirements per person per day based on a 2000 kcal diet.